Feedback Loop Adaptation Speed Feedback Systems for PMSMs via Angle Filtering and Acceleration Stabilization Techniques - Kim, Seok-Kyoon; Lim, Sun; Lee, Kyo-Beum (IEEE transactions on industrial electronics (1982), 2023)
This article presents an advanced solution to the speed tracking problem of permanent magnet synchronous motors (PMSMs) subject to the following two practical concerns: uncertain motor parameter values, load variations, and current feedback dependence level. The results present a few contributions for industrial application: first, a parameter-independent angle filter (providing speed and acceleration estimates) by modifying the structure of the conventional extended state observer, second, the angle filter-based pole-zero cancellation acceleration stabilizer removing the q -axis current dependence of the speed loop to secure the current sensor fault tolerance, and third, the adaptive speed loop in the analytic form to improve the tracking performance by boosting feedback gain during only the transient periods. Using a dynamo testbed adopting a 700-W PMSM as the test motor, this experimental study verifies the effectiveness of the proposed technique under various operating modes.